Analysis of Plane-Parallel Electron Beam Propagation in Different Media by Numerical Simulation Methods; Russian Physics Journal; Vol. 60, iss. 12 - Miloichikova I. A. Irina Alekseevna; Bespalov V. I. Valery Ivanovich; Krasnykh A. A. Angelina Aleksandrovna; Stuchebrov S. G. Sergey Gennadevich; Cherepennikov Yu. M. Yuriy Mihaylovich; Dusaev R. R. Renat Ramilyevich (2018, 2018)
Title screen